"By its very presence": Conventionality and commonality in Shashi Deshpande's realism. (June 2017) - Ben-Yishai, Ayelet
Shashi Deshpande's persistent realism has gone largely unmarked in the scholarship on her work and yet provides an important example of the ways in which the Indian novel in English has continued to rewrite, rework, and yet ultimately keep up a dominant realist capacity. Reading her 1996 novel, A Matter of Time, I argue that Deshpande explicitly rejects a modernist and postcolonial aesthetic in favour of a pedestrian and decidedly conventional realism. In so doing, Deshpande favours the social over the metaphysical as the location of meaning, reanimating realism as an internal communal process of social and cultural inquiry. Reality, the novel seems to offer through its realism, is found not by a search for absent meaning or metaphysical depth, but by recognizing it in its shared social surface and conventional presence.